Review of the Registration and Establishment of a Database for Pregnant Mothers With Cardiovascular Diseases - Mahdi Zahedi; Moghadaseh Jahanshahi; Ahmad Tafaghod‐Hassanpour (Health Science Reports, 2025)
ABSTRACT Background and Aims Cardiovascular diseases (CVDs) cause most maternal deaths, mainly from cardiomyopathies, pulmonary hypertension, aortic dissections, and MIs. We examined CVD prevalence in pregnancy, its links to risk factors/demographics, and identified high‐risk cases for prevention programs. Methods This descriptive study was conducted on 104 pregnant patients with heart conditions referred to Shahid Sayyad Shirazi Educational and Medical Center. The data and information for this project were obtained by reviewing the medical records of pregnant patients with heart conditions and recording this information in the Hospital Information System (HIS) and then subjected to data analysis. Results A total of 104 patients were enrolled. The study revealed that RVH, TTF, and PI diseases had a statistically significant association with a family history of heart disease in pregnant individuals, or with pulmonary HTN, there was a meaningful connection to hypertension. Furthermore, valvular disease MVP and LV enlargement showed a significant association with hyperlipidemia. However, a history of smoking did not have a meaningful association with any of the examined diseases. Additionally, increasing age had a statistically significant correlation with most of the investigated diseases. Conclusions The results obtained from this study indicate that heart diseases in pregnant mothers are an extremely important and undeniable issue, underscoring the significance of thorough examination and care for patients before, during, and after pregnancy. Additionally, it highlights the assessment and early identification of risk factors in these individuals. Therefore, one of the most crucial steps in preserving the health of these patients, in addition to identifying and mitigating risk factors using the mentioned diagnostic methods, is to provide necessary awareness regarding reproductive health and appropriate pregnancy prevention methods.